Identification and Characterization of Fungi Associated with Shrimp from Whiteleg Shrimp Ponds in East Java - Fika Zahroh; Shierly Zaissiliya Clarissa Lifani; Rentienna Rachmadhany; Ayu Safira; Rama Nia Julia Putri; Noerita Widya Melati; Yunita Ika Putri Puspitasari; Maria Agustina Pardede (Journal of Fish Health, 2026)
Fungal infections in shrimp are one of the main challenges in shrimp farming activities that have the potential to reduce productivity levels and crop quality. Fungi are known as opportunistic microorganisms that can cause serious problems, especially when pond environmental conditions are not supportive. Fungal attacks generally occur when shrimp experience physiological stress due to temperature fluctuations, changes in salinity, decreased water quality, or excessively high stocking densities. This study was conducted to identify and characterize the types of fungi associated with shrimp ponds in three main cultivation areas in East Java, namely Banyuwangi, Jember, and Gresik. The fungal isolation process was carried out using Sabouraud Dextrose Agar (SDA) media and incubated at 27°C. Morphological identification was carried out by observing the characteristics of colonies, the shape and color of hyphae, and the structure of conidia. The results of the observations obtained were 6 fungal isolates divided into two main groups, namely yeast including Candida sp., Rhodotorula sp., and Brettanomyces sp. The most commonly found mold species were Aspergillus flavus, Aspergillus fumigatus, and Aspergillus niger. The results of this study demonstrate the potential of fungal probiotics in shrimp farming ecosystems and serve as a basis for developing disease prevention strategies for whiteleg shrimp in East Java's shrimp ponds.